2020
DOI: 10.1002/eji.202048668
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells crosstalk with B cells in the gut and sustain IgA response in the inflamed intestine

Abstract: B lymphocytes are among the cell types whose effector functions are modulated by mast cells (MCs). The B/MC crosstalk emerged in several pathological settings, notably the colon of inflammatory bowel disease (IBD) patients is a privileged site in which MCs and IgA+ cells physically interact. Herein, by inducing conditional depletion of MCs in red MC and basophil (RMB) mice, we show that MCs control B cell distribution in the gut and IgA serum levels. Moreover, in dextran sulfate sodium (DSS)‐treated RMB mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
10
1
Order By: Relevance
“…Regarding IgA and IgM, stress decreases IgA+CD45+ cells, B cells, and plasmablasts (which could explain the general drop in total plasmablasts) but increases IgM+ B cells. However, the DSS model caused an increment in IgA+ cells and a drop in IgM+ 45 , contrary to our results. A feasible explanation relies on the disease stage simulated by our sub-chronic stress model.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding IgA and IgM, stress decreases IgA+CD45+ cells, B cells, and plasmablasts (which could explain the general drop in total plasmablasts) but increases IgM+ B cells. However, the DSS model caused an increment in IgA+ cells and a drop in IgM+ 45 , contrary to our results. A feasible explanation relies on the disease stage simulated by our sub-chronic stress model.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous work (5) established a prominent requirement for LTβR signaling in PP cDC2 and DN cDC homeostasis, and we confirmed Tph1 + mast cells promote cDC2 positioning in SED and the IgA response Mast cells have been implicated as a source of the GPR35 ligand 5-HIAA at sites of inflammation (11,13,22). Moreover, mast cells can augment intestinal IgA responses during inflammation (23). We therefore investigated the impact of mast cell deficiency on the PP IgA response.…”
Section: Gpr35 In Cdcs Is Required For Pp and Intestinal Igasupporting
confidence: 65%
“…Pucillo and colleagues further reported that the CD40/CD40Lmediated MC/B cell contact, together with IL-6 secretion by MCs differentiates B cells to CD138 + plasma cells and IgA secretion [114]. The same group demonstrated the MC/B cell crosstalk in the inflamed colon of inflammatory bowel disease (IBD) patients and by using MC depleted mice, confirmed in vivo, a role for MCs in the control of B cell distribution in the gut, and in the increased IgA production upon dextran sulfate sodium (DSS)-colitis [119]. In vitro, MCs regulated splenic B cells, while peritoneal B cells were unresponsive but skewed the MCs to increased IL33 receptor expression and TNF production [116].…”
Section: Functions In B Cell Activationmentioning
confidence: 83%